2015
DOI: 10.4103/0974-9233.150634
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and clinical outcomes of bacterial and fungal scleritis at a tertiary eye care hospital

Abstract: Purpose:The aim was to analyze demographics, risk factors, pathogenic organisms, and clinical outcome in cases with microbiologically proven bacterial or fungal scleritis.Materials and Methods:Retrospective review of all the medical records of patients with microbiologically proven infectious scleritis examined from March 2005 to December 2009 in the cornea services of L. V. Prasad Eye Institute, Hyderabad, India was done.Results:Forty-two eyes of 42 patients were included in this study. The mean age at presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 36 publications
0
38
2
1
Order By: Relevance
“…Generally, bacterial scleritis develops within 1 month, while fungal scleritis develops after 2 to 3 months (Table 2 ). Since 4 out of the 9 reported cases exhibited recurrences after a transient improvement, this suggests that these types of infections require not only extensive but also prolonged systemic and topical medical treatment especially for fungal scleritis [ 26 ]. All of the gram-positive cocci cases recovered after antibiotic treatment and exhibited good visual outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, bacterial scleritis develops within 1 month, while fungal scleritis develops after 2 to 3 months (Table 2 ). Since 4 out of the 9 reported cases exhibited recurrences after a transient improvement, this suggests that these types of infections require not only extensive but also prolonged systemic and topical medical treatment especially for fungal scleritis [ 26 ]. All of the gram-positive cocci cases recovered after antibiotic treatment and exhibited good visual outcome.…”
Section: Discussionmentioning
confidence: 99%
“…3, 79 It is commonly associated with prior ocular surgery, often following pterygium surgery, and can occur years after the inciting surgey, and this has been reported in large case series in both the developing and developed world. 7, 10, 11 Fewer studies have focused on outcomes after infectious scleritis compared to autoimmune scleritis. In general, older studies reported poor outcomes after infectious scleritis with 42–88% of patients ending up with severe vision loss (< 20/200) and 22–33% requiring enucleation or evisceration despite medical and surgical intervention.…”
Section: Introductionmentioning
confidence: 99%
“…28 Clasdosporium spp. on the other hand, causes Clasdosporium Keratitis 29 while Cercosporium spp is also a known cause of ocular infections. Another potential means that could be contributing to the contaminations observed is poor storage practices.…”
Section: Discussionmentioning
confidence: 99%